2010
DOI: 10.1590/s0004-27492010000400009
|View full text |Cite
|
Sign up to set email alerts
|

Importance of intraocular pressure measurement at 6:00 a.m. in bed and in darkness in suspected and glaucomatous patients

Abstract: Importance of intraocular pressure measurement at 6:00 a.m. in bed and in darkness in suspected and glaucomatous patients A importância da medida da pressão intraocular às 6 horas no leito e no escuro em suspeitos e portadores de glaucoma SEBASTIÃO (1)(2)(3)(4) . Recently, it was demonstrated in the Advanced Glaucoma Intervention Study (AGIS) that long-term IOP fluctuation is associated with a progression of visual field loss in patients with low mean IOP but not in patients with high mean IOP (5) .This fac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 18 publications
0
17
0
Order By: Relevance
“…One definition refers to the difference between the highest and lowest IOP values over a given period, with measurements occurring on different days 14. Alternatively, numerous studies define IOP fluctuation as the SD in IOP over a given time 1 2 11 13 15–22…”
Section: Long-term Iop Fluctuationmentioning
confidence: 99%
See 1 more Smart Citation
“…One definition refers to the difference between the highest and lowest IOP values over a given period, with measurements occurring on different days 14. Alternatively, numerous studies define IOP fluctuation as the SD in IOP over a given time 1 2 11 13 15–22…”
Section: Long-term Iop Fluctuationmentioning
confidence: 99%
“…Another continually referenced issue is that single IOP measurements reflect IOP only at a given instant, which could alter IOP-related calculations 13 14 28 62 63. Multiple studies report that peak IOPs tend to occur outside of normal office hours, limiting the use of office hour curves 8 36 53 54 64.…”
Section: Problems With Iop Analysismentioning
confidence: 99%
“…However, it is well known that IOP measurements during office hours underestimate the IOP peak over 24 hours. 11,23 Finally, some authors have established strong correlations between the IOP peak obtained in the 24-hour DTC and the WDT, 6 but none aimed at investigating the agreement between the measurements. Sakata et al performed a WDT and 24-hour DTC in 33 normal tension glaucoma patients, and found a moderate correlation (r = 0.422) between the IOP peaks detected by both methods.…”
Section: Discussionmentioning
confidence: 99%
“…Later, Drance reported that almost half of glaucoma patients had IOP peaks at 6 a.m., which were detected through a 24-hour IOP curve (4) . The IOP peaks frequently occur upon waking and can be detected at 6 a.m. in darkness and with the patient in a supine position (5,6) . Because of the difficulties in taking measurements for the 24-hour IOP curve in clinical practice, the diurnal IOP curve was proposed as an option to evaluate the IOP profile of glaucoma patients.…”
Section: Introductionmentioning
confidence: 99%